Evaluation of the termolosa system between experimental measurement and calculation with Normative NMX-C-460-ONNCCE-2009 - Ruiz Torres, Raúl Pavel (Centro Universitario de Arte, Arquitectura y Diseño, 2019)
The evaluation of the prefabricated roof component called "Termolosa" is presented, comparing the results of the thermal resistance (R), using the thermal conductivity data obtained based on the ASTM C177-97 standard (stable state test method by means of Guarded-Hot-Plate Apparatus), and the one calculated by the Mexican standard NMX-C-460-ONNCCE-2009, Construction industry, thermal insulation-value "R" for housing envelopes by thermal zone for the Mexican Republic, specifications and verification, The results indicate that the variations are due to the values ​​indicated in the standard, obviating that there are differences in properties between the materials used for the construction, so that the Thermal Resistance is different and for Therefore, when applied with the calculation in standards such as NOM-020-ENER-2011, Energy efficiency in buildings, the heat gain values ​​in the envelope are different.